Genomic evaluation of oxalate‐degrading transgenic soybean in response to Sclerotinia sclerotiorum infection. (10th April 2014) - Calla, Bernarda; Blahut‐Beatty, Laureen; Koziol, Lisa; Zhang, Yunfang; Neece, David J.; Carbajulca, Doris; Garcia, Alexandre; Simmonds, Daina H.; Clough, Steven J.
Summary Oxalate oxidases (OxO) catalyse the degradation of oxalic acid (OA). Highly resistant transgenic soybean carrying an OxO gene and its susceptible parent soybean line, AC Colibri, were tested for genome‐wide gene expression in response to the necrotrophic, OA‐producing pathogen Sclerotinia sclerotiorum using soybean cDNA microarrays. The genes with changed expression at statistically significant levels (overall F‐test P‐value cut‐off of 0.0001) were classified into functional categories and pathways, and were analysed to evaluate the differences in transcriptome profiles. Although many genes and pathways were found to be similarly activated or repressed in both genotypes after inoculation with S. sclerotiorum, the OxO genotype displayed a measurably faster induction of basal defence responses, as observed by the differential changes in defence‐related and secondary metabolite genes compared with its susceptible parent AC Colibri. In addition, the experiment presented provides data on several other transcripts that support the hypothesis that S. sclerotiorum at least partially elicits the hypersensitive response, induces lignin synthesis (cinnamoyl CoA reductase) and elicits as yet unstudied signalling pathways (G‐protein‐coupled receptor and related). Of the nine genes showing the most extreme opposite directions of expression between genotypes, eight were related to photosynthesis and/or oxidation, highlighting the importance of redox in the control of this pathogen.